Linking NRP2 With EMT and Chemoradioresistance in Bladder Cancer - Schulz, Alexander; Gorodetska, Ielizaveta; Behrendt, Rayk; Fuessel, Susanne; Erdmann, Kati; Foerster, Sarah; Datta, Kaustubh; Mayr, Thomas; Dubrovska, Anna; Muders, Michael H. (Frontiers in Oncology, 2020)
Neuropilin-2 (NRP2) is a prognostic indicator for reduced survival in bladder cancer (BCa) patients. Together with its major ligand, vascular endothelial growth factor (VEGF)-C, NRP2 expression is a predictive factor for treatment outcome in response to radiochemotherapy in BCa patients who underwent transurethral resection. Therefore, we investigated the benefit of combining cisplatin-based chemotherapy with irradiation treatment in the BCa cell line RT112 exhibiting or lacking endogenous NRP2 expression in order to evaluate NRP2 as potential therapeutic target. We have identified a high correlation of NRP2 and the Glioma-associated oncogene family zinc finger 2 (GLI2) transcripts in the cancer genome atlas (TCGA) cohort of BCa patients and a panel of 15 human BCa cell lines. Furthermore, we used in vitro BCa models to show the transforming growth factor-beta 1 (TGFβ1)-dependent regulation of NRP2 and GLI2 expression levels. Since NRP2 was shown to bind TGFβ1, associate with TGFβ receptors and enhance TGFβ1 signaling, we evaluated downstream signaling pathways using an epithelial to mesenchymal (EMT)-assay in combination with a PCR profiling array containing 84 genes related to EMT. Subsequent target validation in NRP2 knockout and knockdown models revealed secreted phosphoprotein 1 (SPP1/OPN/Osteopontin) as a downstream target positively regulated by NRP2.